A Case of Guillain-Barré Syndrome and Stevens-Johnson Syndrome/Toxic Epidermal Necrosis Overlap After Pembrolizumab Treatment - Tomoyo Oguri MD, PhD; Shinji Sasada MD, PhD; Satoko Shimizu MD; Risa Shigematsu MD; Yumi Tsuchiya MD; Kota Ishioka MD; Saeko Takahashi MD, PhD; Koichi Oki MD, PhD; Yoshifumi Kimura MD, PhD; Reishi Seki MD; Shigemichi Hirose MD, PhD; Morio Nakamura MD, PhD (SAGE Publishing, 2021)
A 76-year-old man was admitted to our hospital with Guillain-Barré syndrome (GBS), presenting with facial palsy, dysarthria, and dysphagia as Grade 3 immune-related adverse events (irAEs) due to pembrolizumab administration for Stage IV lung adenocarcinoma. Although prednisolone (1 mg/kg) was started for GBS due to the irAE, dark erythema and skin eruptions appeared on the patient's torso. Then erosion was observed on 18% of the body surface area and skin biopsy was performed. Finally, the patient was diagnosed with Stevens-Johnson syndrome/toxic epidermal necrosis overlap. Intravenous immunoglobulin therapy was started, and the skin symptoms improved, with the erosion becoming epithelial. He died of aspiration pneumonia related to GBS, although his neurological symptoms had improved after steroid and intravenous immunoglobulin therapy. This is the first reported case of pembrolizumab-induced GBS and Stevens-Johnson syndrome/toxic epidermal necrosis overlap. It is necessary to be careful that the possibility of other severe irAEs may occur simultaneously.